2016
DOI: 10.1371/journal.pone.0154919
|View full text |Cite
|
Sign up to set email alerts
|

Ck2-Dependent Phosphorylation Is Required to Maintain Pax7 Protein Levels in Proliferating Muscle Progenitors

Abstract: Skeletal muscle regeneration and long term maintenance is directly link to the balance between self-renewal and differentiation of resident adult stem cells known as satellite cells. In turn, satellite cell fate is influenced by a functional interaction between the transcription factor Pax7 and members of the MyoD family of muscle regulatory factors. Thus, changes in the Pax7-to-MyoD protein ratio may act as a molecular rheostat fine-tuning acquisition of lineage identity while preventing precocious terminal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Activation of the caspase 3 protease contributes to Pax7 degradation via targeted cleavage of Pax7 ( 64 , 65 ). This process is impacted by CK2, which phosphorylates Pax7 in the vicinity of the caspase 3 cleavage site and sterically inhibits caspase 3 activity ( 64 , 66 , 67 ). CK2 phosphorylation of Pax7 therefore promotes myoblast proliferation as well as satellite cell renewal.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the caspase 3 protease contributes to Pax7 degradation via targeted cleavage of Pax7 ( 64 , 65 ). This process is impacted by CK2, which phosphorylates Pax7 in the vicinity of the caspase 3 cleavage site and sterically inhibits caspase 3 activity ( 64 , 66 , 67 ). CK2 phosphorylation of Pax7 therefore promotes myoblast proliferation as well as satellite cell renewal.…”
Section: Discussionmentioning
confidence: 99%
“…CK2 kinase activity has been described to target members of both the MRF and paired box (Pax)3 and 7 families via either direct phosphorylation or phosphorylation of their transcriptional regulators and protein partners (24)(25)(26)(27)(28)(29)(30)(31) and to be mainly involved in promoting muscle precursor cell proliferation (27,28,(30)(31)(32). However, the role of CK2 in the progression of the myogenic program and skeletal muscle formation is still to be investigated.…”
mentioning
confidence: 99%
“…Work from our group and many others have demonstrated that CK2 is implicated in myoblast function [17,[45][46][47][48][49][50][51][52][59][60][61]. Specifically, we demonstrated that CK2 modulates the ability of Brg1 to promote myoblast proliferation by inducing Pax7 expression [17].…”
Section: Brg1 and Ck2 Co-localize In Mitotic Cells In Developing Somimentioning
confidence: 58%
“…CK2-mediated regulation of myoblasts occurs at multiple levels. For instance, transcription factors from the myogenic regulatory factor (MRF) family and paired box (Pax) 3 and 7 are directly or indirectly regulated by CK2 activity [17,[45][46][47][48][49][50][51][52]. These proteins are necessary for the proliferation and/or differentiation of muscle-specific precursor cells [46,[53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%